Primary Synovial Sarcoma of Kidney: A Rare Differential Diagnosis of Renomegaly. (24th December 2014) - Modi, Gaurang; Madabhavi, Irappa; Panchal, Harsha; Anand, Asha; Patel, Apurva; Parikh, Sonia; Revannasiddaiah, Swaroop
Abstract : Synovial sarcomas (SS) are classified as subgroup of soft tissue sarcomas affecting mainly extremities of young adults. Primary SS of kidney are very rare tumours with poor prognosis. Though they have characteristic histology and immunohistochemistry (IHC) due to rarity of incidence it is difficult to diagnose them. Sometimes chromosomal rearrangement studies are required to confirm the diagnosis. We are presenting a case of 41-year-old male who was referred to our cancer centre for evaluation of left renal mass. CT scan of abdomen revealed a large left renal mass encasing the aorta. Biopsy of renal mass revealed poorly differentiated sarcoma and IHC was positive for vimentin, CD99, and BCL2 and negative for AE1, epithelial membrane antigen, and leukocyte common antigen. The patient was clinically inoperable as renal mass was encasing the aorta. So he was subsequently offered palliative chemotherapy in form of ifosfamide and adriamycin. CT abdomen shows partial response after 3 cycles of chemotherapy according to RECIST criteria.